METHODS FOR ENHANCING STUDENTS’ CREATIVE ACTIVITY IN ACADEMIC DRAWING CLASSES (British Journal of Global Ecology and Sustainable Development, 2026)
This article examines methods for enhancing students’ creative activity in academic drawing classes, focusing on the pedagogical, cognitive, and artistic foundations of creative engagement within the practice of pencil drawing. Academic drawing is approached not merely as a technical discipline aimed at mastering form, proportion, and tonal relationships, but as a formative artistic process that actively shapes creative thinking and individual expression. From an authorial perspective, creative activity in drawing emerges through the interaction of perceptual sensitivity, analytical observation, and interpretive freedom, rather than through mechanical repetition of academic exercises. The study critically analyzes traditional and contemporary methodological approaches to drawing instruction, identifying the limitations of rigid academic models that prioritize technical accuracy over creative exploration. Using a theoretical-analytical framework grounded in art pedagogy, aesthetics, and creative psychology, the article demonstrates that students’ creative activity can be significantly enhanced through methods that integrate perceptual inquiry, problem-based tasks, and reflective artistic decision-making. The findings suggest that academic drawing classes provide a unique pedagogical space for cultivating creative agency when instructional methods are oriented toward the activation of students’ imaginative and interpretive capacities. The article concludes that the systematic incorporation of creativity-oriented methods into drawing instruction is essential for the development of artistically competent and creatively autonomous practitioners.